Educating fathers to improve exclusive breastfeeding practices: a randomized controlled trial - Farideh Panahi; Farzaneh Rashidi Fakari; Soheila Nazarpour; Razieh Lotfi; Mitra Rahimizadeh; Maliheh Nasiri; Masoumeh Simbar (BMC, 2022)
Abstract Background Fathers' involvement is crucial for promoting breastfeeding. There are a few studies on the effectiveness of fathers' educational programs to promote exclusive breastfeeding. This study aims to assess the effectiveness of a fathers' educational program on their support for breastfeeding, mothers' breastfeeding practice, and exclusive breastfeeding status. Methods This was a randomized controlled trial on 76 fathers who were randomly assigned to two groups of intervention and control, in a selected health center in Iran, 2018. The tools for data collection were: 1) a questionnaire for "Demographic and Maternal-Infant Information"; 2) a questionnaire to assess "Fathers' support for Breastfeeding", and 3) an observational checklist to assess "Mothers' Breastfeeding Practice"; and 4) a questionnaire to assess "Exclusive Breastfeeding Status". The questionnaires were filled up through an interview. The checklist was completed through observation by the researcher. The fathers (with the mothers) of the intervention group were educated using individual face-to-face education and counseling, in two sessions, with the duration of about 40 min and one-week interval, whereas, the fathers of the control group did not receive any education and only mothers were educated with the same instruction. The content of the education was: fathers' education about "benefits of breast milk" and "the supporting ways for breastfeeding including the women encouragement". Then, the scores of "father's support for breastfeeding", "mothers' breastfeeding practice" and "exclusive breastfeeding status" were compared before and after 4 months of intervention in each group, and also between groups. Data were analyzed using SPPS-23, and t- and paired-tests, Chi-square, and Generalized-Estimating-Equations (GEE) tests. Results The results showed two groups were not significantly different regarding the demographic and any other possible confounding variables before the intervention (P < 0.05). The before and after comparisons also demonstrated significant improvements in the two variables including "father's support for breastfeeding", and "mothers' breastfeeding practice after 4 months, in the intervention group (Paired t-test: P<0.001 and P<0.0001, respectively) however, there was a significant decrease in "father's support for breastfeeding" and no improvement in "mothers' breastfeeding practice" after 4 months in the control group (Paired t-test: P < 0.001 and P = 0.07, respectively). Between groups comparison showed also significant higher scores for "father's support for breastfeeding", "mothers' breastfeeding practice" and "exclusive breastfeeding status" in the intervention group comparing to the control group, after 4 months (T-test: P < 0.001 and P < 0.0001; Chi2: P < 0.001, respectively). The interaction effects of time and group were significant in the GEE test for the fathers' support for breastfeeding (B-group = 31.93, B-time = 22.15, p < 0.001) and mothers' breastfeeding practice (B-group = 26.32, B-time = 12.86, p < 0.0). Conclusion The results showed that the father's education improves mothers' breastfeeding practice and increases the rate and continuity of exclusive breastfeeding. Trial registration IRCT201508248801N10. "31/08/2016".